The reform of unemployment protection insurance, 1993-2007 : the erosion of legislated rights in France, Germany, Portugal and Spain - Arcanjo, Maria Manuela (2010)
In the extensive literature that has been dedicated during the past fifteen years to the analysis of the reform of the welfare states, a significant number of studies have focused on the characterisation of the nature and direction of the changes in the main social programmes. This article seeks to contribute to this debate by analysing the reform of unemployment insurance schemes between 1993 and 2007 in France, Germany, Portugal and Spain, as representative of the conservative regime. A comparative analysis is carried out by examining the major legislative amendments concerning eligibility criteria and entitlement conditions, as they are expressed by legislation in the four countries. The findings of the study indicate that the four countries have adopted different instruments at different moments in time, while no significant differences were detected between them, and that the legislative changes introduced in the four insurance schemes may be seen to constitute a real erosion of social rights.